Efectiveness Of Performance Allowances In Improving Work Motivation ASN Secretariat Area Bolaang Mongondow District South - Nurkartini; Sukarman Kamuli; Yakop Noho Nani; Yanti Aneta; Rustam Tohopi (Cita konsultindo, 2025)
This study focuses on the Effectiveness of Regional Performance Allowances on Increasing the Motivation of Civil Servants of the Regional Secretariat of South Bolaang Mongondow Regency by examining the Effectiveness with the concept of Program understanding, Target accuracy, Timeliness, Goal achievement, and Real Change. First, Program understanding, that the work program can increase the sense of belonging and work motivation, Understanding the work program is important because performance assessment is the basis for granting performance permits and a good understanding of the program can increase motivation to achieve performance targets . Second, Target accuracy is very important so that ASN can work effectively and efficiently which ultimately affects the performance assessment and allowances received, the suitability between the targets and objectives of the work program is very important to ensure that ASN efforts are in line with organizational goals that can affect motivation and performance allowances, achieving good work program goals and targets can have an impact on improving work performance and motivation. Third, on time, Program Implementation is related to Performance Allowances that punctuality is a performance indicator that can affect performance and motivation. Fourth, Achievement of goals, In the indicator of achieving goals , there must be alignment between program implementation and the goals that have been implemented. This alignment is important to ensure the effectiveness of the program can affect performance assessments and permits received. Fifth Real Change, real change as a result of the program. The success of the ASN work program will affect work motivation, performance allowances received by ASN actually bring changes in terms of ASN discipline and productivity.